Secondary Metabolites from Aquilaria subintegra Leaves and their Radical Scavenging Activity - Saripah Salbiah Syed Abdul Azziz, Yuhanis Mhd Bakri (Tanjung Malim, 2024)
Secondary Metabolites from Aquilaria subintegra Leaves and their Radical Scavenging Activity by Saripah Salbiah Syed Abdul Azziz, Yuhanis Mhd Bakri